Clinical significance of ectopic inner foveal layers in patients with idiopathic epiretinal membranes. (October 2018) - Doguizi, Sibel; Sekeroglu, Mehmet; Ozkoyuncu, Dilara; Omay, Aslihan; Yilmazbas, Pelin
Abstract Background/Objectives To evaluate the relationship between the presence of ectopic inner foveal layers (EIFL), choroidal thickness, and visual acuity (VA) in patients with epiretinal membranes (ERM) staged by spectral-domain optical coherence tomography (SD-OCT). Subjects/Methods A total of 242 eyes of 121 patients with unilateral idiopathic ERM were prospectively evaluated. ERM stages were defined based on the SD-OCT staging system as stage 1: negligible morphological or anatomical disruption, retinal layers, and foveal pit are identified; stage 2: characteristic stretching of the outer nuclear layer, absence of foveal depression, retinal layers are identified; stage 3: continuous EIFL crossing the central foveal area, absence of foveal depression, retinal layers are identified; and stage 4: anatomical disruption of the fovea, continuous EIFL crossing the entire foveal area, retinal layers are distorted. Results Of 121 eyes with ERM, 23.1% had stage 1, 26.5% had stage 2, 39.7% had stage 3, and 10.7% had stage 4 disease. VA was better in eyes with stage 1 or 2 ERM than stage 3 or 4 ERM (p  < 0.001). VA in logMAR was positively correlated with central foveal thickness (r  = 0.557, p  < 0.001) and EIFL thickness (r  = 0.526, p  < 0.001), but not with an outer nuclear layer thickness (r  = 0.233, p  = 0.123). In multivariate analysis, the presence of EIFL was an independent predictor of VA in eyes with ERM (p  < 0.001). The presence and stage of ERM did not have a significant effect on choroidal thickness (p  > 0.05). Conclusions The SD-OCT staging system according to the presence of EIFL is effective for grading retinal damage and visual loss in eyes with ERM.